Structural behaviour of steel fabric reinforced concrete wall panel under eccentric loading / Ruzitah Supinyeh - Supinyeh, Ruzitah (2009)
Recently reinforced concrete walls have gained greater acceptance from many countries in conjunction with the Industrialized Building System (IBS). Essentially, the system gives an advantage in reducing the dependency of foreign labour and a better investment in technologies, techniques and processes of construction. Steel fabric reinforced concrete wall panel has been used in Malaysia in the past few years and can still be considered as a new construction method. This type of wall may require sequential analysis in making an effective product that gives advantages in all aspects and gives better performance. This research involved laboratory experimental work and model by using a finite element computer program as comparison of the results. Laboratory works tested eight wall samples with size of 1.0 m x 1.5 m and 0.75 m thick. (Length;Height:Width). The wall samples reinforced with double layer steel fabric size B7 with yield strength of 510 N/mra2 and concrete Grade 30. The wall panel tested under axial load with the eccentric t/6 or 12.5 mm of wall thickness. Variations of support condition include oft/6 with pinned or fixed imposed at the top and bottom of the wall panel. The analysis of the wall panel model yielded from the computer program PROKON of version 2.4 by using a 3-dimensional model of the wall panel. It was modeled as support condition pin on top and fixed at the bottom of the wall.